Dejerine-Roussy Syndrome: Understanding Chronic Thalamic Pain - Saket S Toshniwal; Jiwan Kinkar; Yatika Chadha; Sourya Acharya; Sunil Kumar (Journal of Clinical and Diagnostic Research)
A 50-year-old male, known to be hypertensive and non compliant with medications, with a significant past history of stroke three months ago, presented to the hospital with chief complaints of persistent burning sensations in his left arm and leg, as well as his entire face. He also reported episodes of sharp shooting pain in these regions lasting for a few seconds. Additionally, he complained of increased sensitivity to touch and intolerance to any painful stimuli, experiencing pain even upon touch, which caused significant discomfort and led to feelings of depression. These complaints have been present since he had a stroke three months ago, and they have gradually progressed to a stage where the pain has become intolerable. A Magnetic Resonance Imaging (MRI) of the brain performed at the time of the stroke showed a lesion in the ventroposterior lateral thalamic region, leading to the diagnosis of the debilitating condition known as Dejerine-Roussy syndrome, as shown in [Table/Fig-1a-d].